Effects of Baicalin on Blood Pressure and Left Ventricular Remodeling in Rats with Renovascular Hypertension - Dai, Hualei (Med Sci Monit, 2017)
BACKGROUND: This study aimed to explore the effect of baicalin, which is a kind of bioactive flavonoid, on blood pressure and left ventricular remodeling in rats with renovascular hypertension. MATERIAL/METHODS: A total of 40 male Wistar rats were randomly assigned into sham-operation (n=10) and renal hypertension model groups (2-kidney-1 clip; 2K-1C, n=30). The rats in the renal hypertension model group were randomly subdivided into 2K-1C (n=13) and 2K-1C/Baicalin groups (n=14). The cardiac function indexes were determined after 4 weeks. The morphological changes in the myocardial tissue were observed using hematoxylin and eosin and Masson staining. The myocardial apoptosis was detected using the terminal deoxynucleotidyl transferase deoxyuridine triphosphate nick-end labeling method, and the expression of C/EBP homologous protein and caspase-3 was monitored by Western blot. The expression of GRP78 and GRP94 in myocardial cells of rats was detected by qPCR and Western blot technology. RESULTS: No significant change in blood pressure was observed in the 2K-1C/Baicalin group compared with the 2K-1C group, but the indexes of left ventricular remodeling significantly improved. Pathological myocardial fibrosis and expression of fibrosis-related factors significantly decreased in the 2K-1C/Baicalin group compared with the 2K-1C group. The expression of glucose-regulated protein (GRP)78, GRP94, CHOP, and caspase-3, and apoptosis of cardiomyocytes also decreased in the 2K-1C/Baicalin group. CONCLUSIONS: Baicalin has no significant antihypertensive effect, but reduced pathological changes in the myocardium, alleviated endoplasmic reticulum stress, and reduced myocardial apoptosis, reverting left ventricular remodeling in rats with renovascular hypertension.